Molecular genetic approaches on cattle and chicken breeding: A Review - H.F.N. Lapian (Universitas Sam Ratulangi, 2023)
In recent years, the application of molecular genetic methods and techniques has made a significant contribution in various fields, including animal husbandry. Traditional approaches to livestock breeding have gained new insights from molecular genetics, resulting in increased efficiency and optimization of breeding programs. Genome selection has emerged as a revolutionary technique, enabling comprehensive selection at the early stages of breeding. Moreover, the manipulation of economically important candidate genes at the cellular level contributes to future advances in livestock breeding. In cattle, the integration of gene editing into breeding programs is considered a tool for genetic modification, with particular emphasis on its potential implications across sectors and regions. Numerous studies on the use of genes as the basis for breeding chickens have been conducted extensively. These studies can be categorized into several sections, such as disease resistance, physical performance, and physiological aspects. The significant contribution of molecular genetics to livestock breeding and genetic improvement still requires further research to capitalize on technological advances in this field. Keywords: Breeding, cattle, chicken, gene selection, molecular genetic